NATO and European security : alliance politics from the end of the Cold War to the age of terrorism - Moens, Alexander, 1959-; Cohen, Lenard J.; Sens, Allen Gregory, 1964- (Humanistic perspectives on international relations., 2003)
From the end of the Cold War to the terrorist attacks on the United States in September 2001, the NATO Alliance has changed profoundly. This book explores the multifaceted consequences of NATO's adjustment to new international and domestic political and security realities. Internal Alliance politics and matters of relative power within the membership have strongly influenced recent NATO developments. Several major issues challenging the Alliance are examined, including how the impact of efforts to develop an enhanced common European security and defense policy have affected NATO: whether missi.